Do financial development and economic openness matter for economic progress in an emerging country? Seeking a sustainable development path - Ammara Hussain; Ammar Oad; Munir Ahmad; Muhammad Irfan; Farhan Saqib (Journal of Risk and Financial Management, 2021)
While emerging economies face the challenge of competing with developed nations, they are capable of catching up to the developed world. In this context, financial development and the degree of economic openness may provide better living conditions for the current generation without giving up future generations' prosperity. Therefore, this research's prime intention is to investigate the impact of economic openness and financial development on economic progress, employing Pakistan's time-series data from 1975-2018. To examine the long-term association between economic openness, financial development, and economic progress, Autoregressive Distributed Lag (ARDL) cointegration tests were performed and the results present a long-term association between these variables. Findings from ARDL estimates indicate that the relationship between financial development and economic progress is significantly positive in the long term. Contrastingly, the relationship between economic openness and economic progress is significantly positive in the short term. A fully modified ordinary least square technique was applied to check the robustness of the long-term links. The Granger causality test revealed that economic progress is motivated by both economic openness and financial development in an emerging economy such as Pakistan. Thus, policies boosting financial development and economic openness are proposed to put the emerging economies on a path of sustainable economic development.
Keywords: 330; ARDL; economic openness; economic progress; financial development; Pakistan